2017
DOI: 10.1093/annonc/mdx149
|View full text |Cite
|
Sign up to set email alerts
|

Identifying an early indicator of drug efficacy in patients with metastatic colorectal cancer—a prospective evaluation of circulating tumor cells, 18F-fluorodeoxyglucose positron-emission tomography and the RECIST criteria

Abstract: Early response based on both PET-CT and CTC analysis has prognostic and probably predictive significance in patients undergoing first-line chemotherapy for metastatic colorectal cancer. Its utility as a new tool for assessing early drug response should be further validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…As a "liquid biopsy" technology, CTC detection is of important value for getting more insights into metastasis-associated progression [7,8]. Our group and others have contributed a considerable body of evidence indicating that CTC detection in peripheral blood has great clinical potential for identifying potentially metastatic disease earlier, monitoring treatment response and evaluating patients' clinical outcome in CRC [9][10][11][12]. In the process of CTC detection, a fact that cannot be ignored is that the number of CTCs in peripheral blood is extremely low, with one CTC in millions of blood cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…As a "liquid biopsy" technology, CTC detection is of important value for getting more insights into metastasis-associated progression [7,8]. Our group and others have contributed a considerable body of evidence indicating that CTC detection in peripheral blood has great clinical potential for identifying potentially metastatic disease earlier, monitoring treatment response and evaluating patients' clinical outcome in CRC [9][10][11][12]. In the process of CTC detection, a fact that cannot be ignored is that the number of CTCs in peripheral blood is extremely low, with one CTC in millions of blood cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, by multivariate analysis, we confirmed that pretreatment HS was an independent prognostic factor for PFS and OS. One possible explanation is that other factors like second-line chemotherapy or change of targeted therapy may be weighted more than pretreatment HS for prolonged OS 6,8,20,23…”
Section: Discussionmentioning
confidence: 99%
“…Tumor response was measured after every 4 cycles by contrast-CT scan and magnetic resonance imaging (MRI) examination and the Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST v1.1) was applied to grade the best response in each case 20. All cases were discussed for eligibility for surgery by a multidisciplinary team including medical oncologists, radiologists and surgical oncologists.…”
Section: Methodsmentioning
confidence: 99%
“…Another significant study of 84 colon cancer patients undergoing chemotherapy showed that changes in the number of CTCs reflected the objective efficacy of the tumor at an early stage, with a sensitivity of 64%, specificity of 70%, and positive predictive value of 74%. Therefore, CTCs have the potential to detect MRD earlier than imaging responses [118].…”
Section: Ctcs and Ctdna As Monitoring Tools For Mrdmentioning
confidence: 99%